Sex Chromosome Complement Contributes to Sex Differences in Bradycardic Baroreflex Response - Caeiro, Ximena Elizabeth (2011)
To investigate whether sex chromosome complement modulates bradycardic baroreflex response and contributes to the angiotensin II-bradycardic baroreflex sex differences, we used the four core genotype mouse model in which the effect of gonadal sex and sex chromosome complement is dissociated, allowing comparisons of sexually dimorphic traits among XX- and XY-females as well as in XX- and XY-males. In conscious gonadectomized (GDX) MF1 transgenic mice we evaluated baroreflex regulation of heart rate in response to changes in blood pressure evoked by phenylephrine (1.0 mg/ml), angiotensin II (100 ìg/ml) and sodium nitroprusside (1 mg/ml). The administration of phenylephrine in GDX-XY-females resulted in a significantly lower baroreflex response when compared to the other genotypes [in beats.min-1.mmHg-1 (slopes of regression lines for GDX-XY-females -3.56 ± 0.37 vs. -6.06 ± 0.38, -6.36 ± 0.54 and -6.70 ± 0.34 for GDX-XY-male, GDX-XX-female and GDX-XX-male mice respectively)] {F(1,19)=9,63; p<0.01}. Besides, in both GDX-XY-males and females, the angiotensin II-bradycardic baroreflex response was attenuated when compared to heart rate changes in GDX-XX-male and female mice [in beats.min-1.mmHg-1 slopes of regression lines: -2.83 ± 0.28 vs. -5.76 ± 0.26 in GDX-XY and GDX-XX mice respectively] {F(1,19)=13,91; p<.005}. In contrast, reflex tachycardic responses to sodium nitroprusside were comparable in all the genotypes. These data support the hypothesis that sex chromosome complement modulates reflex inhibition of heart rate to phenylephrine and angiotensin II. Elucidating the foundational sources of sexually dimorphic traits in the regulation of baroreceptor reflex may enable the design of more appropriate sex-tailored therapeutic treatments in the future.